2006
DOI: 10.1007/s10765-006-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Low-Density Pure Alkanes and Their Binary Mixtures Calculated by Means of an (n-6) Lennard-Jones Temperature-Dependent Potential

Abstract: Self-consistent calculations of interaction pVT-virial coefficients B 12 (T ), viscosities η mix (T ), and diffusion coefficients D 12 (T ) of binary mixtures of the alkanes C n H 2n+2 (n < 6) are presented. This study is based on the recently developed model of the (n-6) Lennard-Jones temperature-dependent potential (LJTDP) and uses already obtained potential parameters of the pure alkanes as input data. The well-known and simple Lorentz-Berthelot (LB) and the more elaborate Tang-Toennies (TT) mixing rules ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 12 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…The LJTDP has been successfully applied before to a number of pure gases like the alkanes , and perfluoroalkanes . We have shown that it performs also very well in the prediction of B , η, and D of binary mixtures of alkanes and other gases. , To give a comprehensive overview on the molecules with sum formula C m H 2 m , we not only consider the alkenes but also try to include the two cyclic compounds cyclopropane (C 3 H 6 ) and cyclobutane (C 4 H 8 ) in our studies. These two molecules are also of some importance in industry and basic research …”
Section: Introductionmentioning
confidence: 99%
“…The LJTDP has been successfully applied before to a number of pure gases like the alkanes , and perfluoroalkanes . We have shown that it performs also very well in the prediction of B , η, and D of binary mixtures of alkanes and other gases. , To give a comprehensive overview on the molecules with sum formula C m H 2 m , we not only consider the alkenes but also try to include the two cyclic compounds cyclopropane (C 3 H 6 ) and cyclobutane (C 4 H 8 ) in our studies. These two molecules are also of some importance in industry and basic research …”
Section: Introductionmentioning
confidence: 99%
“…Once R mAA (eff) ( T ), ε AA (eff) ( T ), and n AA are known for the pure substances, the parameters R mAB (eff) ( T ), ε AB (eff) ( T ), and n AB describing the interaction between unlike molecules can be deduced via mixing rules. In this work, we use our recently developed Hohm−Zarkova−Damyanova (HZD) mixing rules . For the unlike interaction parameters we have with and where α A and α B are the dipole-polarizabilities and C 6 AA and C 6 BB are the dispersion-interaction energy constants of molecules A and B, respectively.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…To handle the vast number of different binary mixtures containing alkanes, mixing rules of the intermolecular interaction potential parameters are often used which relate the unlike interaction AB between two particles A and B to the like interactions AA and BB . Although it is now accepted that the very simple Lorentz−Berthelot mixing rules do not give the correct potential parameters of unlike interactions, they are still widely used because in some cases they nevertheless allow for a reliable prediction of some thermophysical properties of binary mixtures. Despite their partial success, in many cases extensions of the Lorentz−Berthelot mixing rules or completely different combination rules give better results for binary alkane mixtures. In our recent work on the thermophysical properties of low-density binary alkane mixtures, we have developed a flexible extension of the physically reasonable Tang−Toennies mixing rules. , This new scheme is called Hohm−Zarkova−Damyanova (HZD) mixing rules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations